Parental Mediation with Adolescent Users of I.T. Devices - Weny Savitri S. Pandia; Margaretha Purwanti; Debri Pristinella (ANIMA Indonesian Psychological Journal, 2019)
A parental strategy in relation to the influence of media usage (parental mediation), in this case that of the Internet on adolescents, is greatly needed. The ideal strategy is a combination of active mediation (discussion regarding the content), and restrictive mediation (determination of rules for media usage), however what is normally employed is still restrictive mediation and co-using mediation (the joint use of media with the child, but without parent-child interaction to explain media content and impact). In this research, the aim was to look at an illustration of parental mediation towards the child. Quantitative research, with purposive sampling was conducted, on 94 parents and 423 information technology-based junior high school students, using questionnaires based upon the Perceived Parental Media Mediation Scale (the reliability of the parental scale being .84, and that of the student scale being .84). From frequency analysis and correlation testing, it was found that the strategy of restrictive mediation was the dominant one used by parents. This was supported by the perceptions of the students. Types of employment, numbers of children, and education levels did not influence the type of parental mediation; however, the greater the ages of parents, the greater was the imposition of restrictions. From the research, a picture may be gained of the allocation of devices to students. Explanation is required, to parents, of the importance of active mediation, and the positive utilization of I.T. devices (hereinafter called ‘devices’) by students.